2012
DOI: 10.1103/physrevb.86.125203
|View full text |Cite
|
Sign up to set email alerts
|

Speeding up the solution of the Bethe-Salpeter equation by a double-grid method and Wannier interpolation

Abstract: 5 pages, 3 figures. Accepted for Phys. Rev. BInternational audienceThe Bethe-Salpeter equation is a widely used approach to describe optical excitations in bulk semiconductors. It leads to spectra that are in very good agreement with experiment, but the price to pay for such accuracy is a very high computational burden. One of the main bottlenecks is the large number of k-points required to obtain converged spectra. In order to circumvent this problem we propose a strategy to solve the Bethe-Salpeter equation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 38 publications
1
60
0
Order By: Relevance
“…(2) up to a kinetic energy cutoff of 4 Ry. The absorption of bulk GaAs is instead computed with a double-grid sampling of the BZ [23] with a regular 12 × 12 × 12 mesh shifted from plus a random mesh of 2000 k points. In this case the well-established value [24] of 0.8 eV opening of the band gap has been used for the QP correction.…”
Section: Optical Properties Of Mn-doped Gaasmentioning
confidence: 99%
“…(2) up to a kinetic energy cutoff of 4 Ry. The absorption of bulk GaAs is instead computed with a double-grid sampling of the BZ [23] with a regular 12 × 12 × 12 mesh shifted from plus a random mesh of 2000 k points. In this case the well-established value [24] of 0.8 eV opening of the band gap has been used for the QP correction.…”
Section: Optical Properties Of Mn-doped Gaasmentioning
confidence: 99%
“…The optical absorption spectra were obtained by solving the Bethe-Salpeter Equation (BSE), [8][9][10] starting from our G 0 W 0 results and employing the double-grid method for k-point sampling. 22 …”
Section: Computational and Experimental Techniques A Ab Initio Cmentioning
confidence: 99%
“…Since BSE calculations generally require a large number of k-points, we employed the double-grid method proposed in Ref. 22 to speed up the convergence. Figure 4 shows the absorption coefficient (α) of Ta 3 N 5 computed at the BSE/G 0 W 0 level of theory, compared with the experimental result obtained with UV-Vis spectroscopy.…”
Section: Optical Spectramentioning
confidence: 99%
“…Due to the light electron mass, which leads to a steep conduction band valley, fully converging the radiative lifetimes in GaAs requires very fine Brillouin zone grids with a large computational cost. Using a double-grid technique, Kammerlander et al [47] have shown that a 40 × 40 × 40 k-point grid is sufficient to converge the BSE absorption spectrum. Since the radiative lifetimes depend on the energy and transition dipole of the lowest-energy excitons, the k-point convergence of the lifetimes is similar to that of the absorption spectrum.…”
Section: Numerical Calculationsmentioning
confidence: 99%
“…Using the standard BSE (without the double-grid technique of Ref. 47), the finest grid we were able to reach is a 30 × 30 × 30 k-point grid, which took over 10, 000 CPU cores to compute. Since our grid is close to the fully converged 40 × 40 × 40 k-point grid, it allows us to obtain results close to convergence.…”
Section: Numerical Calculationsmentioning
confidence: 99%